Shrimp Culture Practices at Farmers Level in Bagerhat District - Chandra, KJ; Chowdhury, AR; Das, DR (Progressive Agriculture, 2013)
A study was conducted on culture practices of shrimp at farmers level in Bagerhat District. Investigation was based on a sample of 123 shrimp farmers from the seven Thanas (Fakirhat, Mollahat, Sadar, Rampal, Mongla, Chitalmari and Kachua) of the District, 73.17% farmers produced shrimp with white fishes. Farmers (54.47%) started to culture during 2000-2004 in this area. The culture period was typically four months for bagda and six to seven months for golda. Hatchery PL are stocked mainly in May to June for prawn and from late March for bagda. The average stocking density of shrimp PL golda and bagda was 24.16 and 12.16 thousand/ha in the farms. Varieties of feeds such as cooked rice, fishmeal, oilcake and snail muscle were used for shrimp culture. Mainly virus disease was responsible for the great loss of shrimp in this area. About 46.34% of the surveyed farms faced a huge damage due to WSBV. The average bagda and golda production was 350.37 kg and 428.08 kg/ha/year. Long term sustainability of shrimp farming facing problems due to lack of money, poor supply of good quality PL, lack of technical knowledge, higher production costs and poor institutional support. It might be however, necessary to establish shrimp hatcheries and provide training facilities, extension service, institutional and policy support to the farmers with the help of DoF and NGOs. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16766 Progress. Agric. 21(1 & 2): 173 - 185, 2010